Phaeochromocytoma found on cardiovascular magnetic resonance in a patient presenting with acute myocarditis: an unusual association. (8th June 2018) - Khattak, Sophia; Sim, Iain; Dancy, Luke; Whitelaw, Benjamin; Sado, Dan
Abstract : Myocarditis is inflammation of the cardiac muscle. The symptoms, signs and basic investigation findings can mimic that of myocardial infarction. The most common cause is infection (most commonly viral). Cardiovascular magnetic resonance (CMR) is the gold standard non-invasive diagnostic test for potential acute myocarditis as it allows assessment of myocardial oedema and scar. A man aged 25 years was admitted with chest pain, dizziness, headache, palpitations and sweating. His troponin was mildly positive. A CMR was performed which showed mild myocarditis and a right suprarenal mass which was confirmed to be a phaeochromocytoma based on biochemistry and a dedicated imaging workup. Phaeochromocytoma can lead to cardiac involvement in the form of left ventricular dysfunction, or catecholamine-induced myocarditis.